2021
DOI: 10.1136/bmjopen-2020-047086
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation in the last month of life and in-hospital death of nursing home residents: a cross-sectional analysis of six European countries

Abstract: ObjectivesTo examine the rate and characteristics of hospitalisation in the last month of life and place of death among nursing home residents and to identify related care processes, facility factors and residents’ characteristics.SettingA cross-sectional study (2015) of deceased residents in 322 nursing homes in six European countries.ParticipantsThe nursing home manager (N=1634), physician (N=1132) and primary nurse (N=1384) completed questionnaires.Outcome measuresHospitalisation and place of death were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Finally, by care need levels, we observed a steeper decreasing trend in in-hospital deaths among those with higher care need levels. This is consistent with findings of previous studies which indicated that a higher care need level or a poorer functional status was negatively associated with in-hospital deaths [ 12 , 20 ]. As the level of care needs deteriorated, the five-year survival rates showed a decline, from 72.3% for people with the least disability support level, to 22.2% for those with care need level 5 (most disabled) [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, by care need levels, we observed a steeper decreasing trend in in-hospital deaths among those with higher care need levels. This is consistent with findings of previous studies which indicated that a higher care need level or a poorer functional status was negatively associated with in-hospital deaths [ 12 , 20 ]. As the level of care needs deteriorated, the five-year survival rates showed a decline, from 72.3% for people with the least disability support level, to 22.2% for those with care need level 5 (most disabled) [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although knowledge of users' care preferences is essential for goal-concordant care, which is a quality indicator of palliative care, the preferences of our residents were poorly known, and their FCs' preferences were often explored too late. These findings confirm the data of a large cross-sectional analysis involving 322 NHs in six European countries, which found that only one-third of residents in Belgium had a 'do not transfer to hospital' advance directive, while barely anyone had similar documentation in Italy [14]. Similarly, our findings are close to those of previous focus group interviews with the FCs of Norwegian NH residents who often did not know their relative's wishes when decisions had to be made and experienced decision-making burden [48].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, our findings are close to those of previous focus group interviews with the FCs of Norwegian NH residents who often did not know their relative's wishes when decisions had to be made and experienced decision-making burden [48]. Poor knowledge of the residents' preferences is recognized to increase the likelihood of intensive care [14]. Instead, when the preferences were known, they were generally comfort-oriented and directed the HCPs towards palliative-oriented care [49].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations